The Effects of Outdoor Source on Pollution Characteristics and Dynamic Changes of Particulate Matter in an Office - Guozhong Zheng; Yuzhen Lu; Yajing Wang; Zhengzheng Zhao; Ke Li; Xutao Zhang (Advances in Civil Engineering)
The indoor air quality has a direct impact on human health. Particulate matter is one of the important factors affecting the indoor air quality. The paper selects an office as the study object and studies the pollution characteristics and dynamic changes of indoor particulate matter in different outdoor pollution levels. The mass concentration of outdoor PM10 is used as the evaluation basis of the outdoor pollution level. The outdoor PM10 concentration levels are divided into the range of 200–300, 300–400, 400–500, 500–600, 600–700 μg·m−3, individually. Firstly, the change characteristics of the mass concentration and the number concentration of the particulate matter in the five outdoor conditions are analyzed. Secondly, the maximum increase values and the maximum increase rates of the mass concentrations of different particle sizes in the five conditions are compared. Then, the penetration factors of the particulates in different sizes are compared among the five conditions. Finally, the correlation between indoor particulate matter and outdoor particulate matter is studied. The study results show that the effect of outdoor infiltration has a great influence on the indoor PM1 mass concentration, and the penetrating factors of the particulate matter between 0.3 μm and 0.5 μm are higher than 0.6; their permeability is the most obvious.